Aplicação da tecnologia 5g em projetos de telefonia - Takemoto, Ivan Morisugi [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This paper presents a study on the current technology used in long term evolution (LTE) telecommunications, based on bibliographic research, the current implementation of 3G and 4G networks in Brazil and the expectation of 5G network in Brazil and in the world. The user behavior has changed, back in past, they used the voice service and nowadays, started using data services and the necessityfor greater speed and the same user have multiple devices to connect, creating a wish for increased volume and speed of the network. The history of the development of technologies in the mobile device, from 1G to 4G and the possible changing needs for 5G, displays the path to the point where we are today at the level of technology. Finally, it presents the current situation of the experiences that you can now enjoy and makes a small projection of what is to meet with the new technology and what will be improvements in the user experience with the implementation of the new 5G technology

Este trabalho apresenta um estudo sobre a tecnologia atual usada em telecomunicações long term evolution (LTE), baseado em pesquisas bibliográficas, a atual implementação das redes 3G e 4G no Brasil e, a expectativa da rede 5G tanto no Brasil quanto no mundo. A mudança de comportamento do usuário que antes usava o serviço de voz e passou a usar serviços de dados e da necessidade de maior velocidade e de um mesmo usuário possuir diversos dispositivos para se conectar, gerando uma necessidade de aumento de volume e velocidade da rede. A história do desenvolvimento das tecnologias no aparelho de celular, desde o 1G até o 4G e as possíveis necessidades de mudança para o 5G, apresenta o caminho até chegar ao ponto onde estamos hoje em nível de tecnologia. Por fim, apresenta o panorama atual das experiências que o usuário já pode desfrutar e, faz uma pequena projeção do que se pretende atender com a nova tecnologia e, quais melhorias haverão na experiência dos usuários com a implementação da nova tecnologia 5G
Application of 5g technology in telephony projects
Keywords: Comunicação móvel; Telefonia celular; Telecomunicações; Cellular telephone systems